Prediction of the mechanical properties of zeolite pellets for aerospace molecular decontamination applications - Rioland, Guillaume; Dutournié, Patrick; Faye, Delphine; Daou, T. Jean; Patarin, Joël (Beilstein Journal of Nanotechnology, 2016)
Zeolite pellets containing 5 wt % of binder (methylcellulose or sodium metasilicate) were formed with a hydraulic press. This paper describes a mathematical model to predict the mechanical properties (uniaxial and diametric compression) of these pellets for arbitrary dimensions (height and diameter) using a design of experiments (DOE) methodology. A second-degree polynomial equation including interactions was used to approximate the experimental results. This leads to an empirical model for the estimation of the mechanical properties of zeolite pellets with 5 wt % of binder. The model was verified by additional experimental tests including pellets of different dimensions created with different applied pressures. The optimum dimensions were found to be a diameter of 10–23 mm, a height of 1–3.5 mm and an applied pressure higher than 200 MPa. These pellets are promising for technological uses in molecular decontamination for aerospace-based applications.
Keywords: design of experiments methodology; mechanical performance; molecular decontamination; operating optimums; zeolite pellets